Experimental Research of the Strength of an Open Wagon Hatch Cover During the Transportation of Containers in it - Panchenko, S. V.; Lovska, A. O.; Pavliuchenkov, M. V.; Rukavishnykov, P. V.; Petrenko, D. H.; Ravlyuk, M. H. (Science and Transport Progress, 2025)
Purpose. The work is aimed at highlighting the peculiarities of experimental studies of the strength of a hatch cover of an open wagon loaded from a fitting stop for fastening containers. Methodology. In order to make it possible to use open wagons for container transportation, an experimental study of the hatch cover of an open wagon loaded from a fitting stop was conducted. Bench tests were conducted in the research laboratory of the “Center for Diagnostics of Transport Structures” at the Ukrainian State University of Railway Transport. The stresses that arise in the design of the hatch cover were determined using the method of electrical strain gage measurement. The installation of strain gauges was carried out according to the bridge scheme. The locations of the strain gauges on the hatch cover were determined based on the theoretically obtained stress fields that arise in the hatch cover. Before installing the strain gauges, they were calibrated. The load on the fitting stop was transmitted through a metal cup that imitated the container fitting. The maximum load transferred to the fitting stop is assumed to be 6 t (60 kN), which corresponds to the maximum loaded state of a container of standard size 1CC. The strain gauge readings were taken using a VNP-8 strain gauge station. Findings. During the research, the maximum stresses in the hatch cover were 345.4 MPa. The obtained stresses exceed the permissible ones, which allows us to conclude that it is impossible to use such a container fastening scheme in practice. The largest percentage of discrepancy between the results of computer modeling and experimental research on the strength of the hatch cover of an open wagon is about 10% and is recorded when the load on the fitting stop is 30 kN. Originality. A procedure for conducting an experimental study of the strength of the hatch cover of an open wagon under the load from the fitting stop for fastening containers is proposed. The dependence of the stresses in the hatch cover of the open wagon on the load it perceives through the fitting stop was obtained. Practical value. The conducted research will contribute to the creation of recommendations for adapting open wagons to container transportation and increasing the efficiency of container transportation.